Ultrasonic technique for measurement of oil-film thickness in metal cold rolling. (3rd April 2022) - Adeyemi, G. J.; Dwyer-Joyce, R. S.; Stephen, J. T.; Adebayo, A.
ABSTRACT: Lubrication is essential in metal cold rolling operation to regulate friction at the metal–roll interface, reduce energy loss and improve the product surface finish. A novel non-intrusive pitch-catch technique, based on the reflection of ultrasound, was employed on a pilot mill to evaluate oil-film thickness at the metal–roll interface during the metal cold rolling operation. During the metal rolling process, oil-film thickness was measured under varying rolling load and rolling speed. The oil-film thickness increases as the roll speed increases and reduces as the rolling load increases. The values of oil-film thickness obtained from this non-intrusive ultrasonic technique agree with theoretical values. This study is a proof of concept and has shown promising results. If further developed, the technique could be employed for in situ monitoring of lubricant during rolling operation in metal rolling industries. GRAPHICAL ABSTRACT: UF0001